Pengaruh Capital Adequacy Ratio, Non Performing Loan dan Return On Asset Terhadap Penyaluran Kredit Usaha Rakyat pada Perusahaan Perbankan Periode 2010 - 2019 - Ramadayanti, Wiwi; Kosasih, Kosasih (Pandawan, 2021)
Bank Rakyat Indonesia, Bank Mandiri, and Bank Negara Indonesia are some of the banking companies that provide small business loans for MSME players with a view to find out the Capital Adequacy Ratio, Non-Performing Loan and Return On Asset in banking companies that distribute people’s Business Loans for the period 2010 - 2019. Researchers used Quantitative research methods with Descriptive and Verification research methods. People’s Business Credit is one of the programs issued by the government to help small communities that have problems with capital. The KUR program is the solution, with a fairly fast, easy process and very little interest. Research result on variables Capital Adequacy Ratio, Non-Performing Loan, and Return On Asset in Banking Companies for the period 2010 - 2019. The results of the study on the Capital Adequacy Ratio variable did not effect on the level of trust and Non-Performing Loan variable there was a negative and significant level on the Business Credit to Banking Companies for the period 2010-2019.